2000
DOI: 10.1007/s11661-000-0207-y
|View full text |Cite
|
Sign up to set email alerts
|

Near-net-shape forming of Al-Al3Ni functionally graded material over eutectic melting temperature

Abstract: A possibility to make near-net-shape functionally graded material (FGM) products has been examined. The FGM billets having a graded volume fraction of Al 3 Ni in thickness direction were machined from an Al-Al 3 Ni FGM thick-walled tube manufactured by a vacuum centrifugal method. Billets, which were set in the container for the backward extruding, were heated to 650 ЊC to 680 ЊC, at which temperature the FGM becomes a mixture of molten aluminum eutectic and solid intermetallics. Then, billets were extruded su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
5
18
0
3
Order By: Relevance
“…If the transition point is expressed as a temperature, it can range from approximately 855 K (582 ˚C) to 857 K (584 ˚C), which is just above the melting point for both materials. This conclusion is similar to those previously reported for Al-Al 3 Ni and Al-Al 3 Fe FGMs [8,9]. To ensure superior mechanical properties of the cast materials, both a moderate working duration and adequate deformation in a high-speed semi-solid forming operation is required.…”
Section: Estimation Of Optimum Forming Conditionsupporting
confidence: 89%
See 3 more Smart Citations
“…If the transition point is expressed as a temperature, it can range from approximately 855 K (582 ˚C) to 857 K (584 ˚C), which is just above the melting point for both materials. This conclusion is similar to those previously reported for Al-Al 3 Ni and Al-Al 3 Fe FGMs [8,9]. To ensure superior mechanical properties of the cast materials, both a moderate working duration and adequate deformation in a high-speed semi-solid forming operation is required.…”
Section: Estimation Of Optimum Forming Conditionsupporting
confidence: 89%
“…To enable the visco-plastic flow analysis of near-net forming of Duralcan F3A.20S, its rheological behavior at high shear rates must be clarified. Moreover, the analysis must be meaningful to confirm the results of semi-solid forming of Al-Al-base intermetallic FGMs reported in our previously papers [8,9]. We observed that the semi-solid forming just above the melting point is adequate to obtain finer intermetallics in the Al-base FGMs.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The vacuum centrifugal method (centrifugal method under evacuated condition) 15) was applied to the alloy and a thickwalled tube with 90 mm diameter  90 mm length  15 mm thickness was manufactured. From the phase diagram of AlFe system, shown in Fig.…”
Section: Materials and Vacuum Centrifugal Methodsmentioning
confidence: 99%